COVID-19 Vaccine Uptake, Acceptance, and Hesitancy Among Persons With Mental Disorders During the Second Stage of China's Nationwide Vaccine Rollout - Huang, Hui; Zhu, Xiao-Min; Liang, Peng-Wei; Fang, Zhong-Ming; Luo, Wei; Ma, Yi-Ming; Zhong, Bao-Liang; Chiu, Helen Fung-Kum (Frontiers in Medicine, 2021)
Persons with mental disorders (PwMDs) are a priority group for COVID-19 vaccination, but empirical data on PwMDs’ vaccine uptake and attitudes toward COVID-19 vaccines are lacking. This study examined the uptake, acceptance, and hesitancy associated with COVID-19 vaccines among Chinese PwMDs during China’s nationwide vaccine rollout. In total, 906 adult PwMDs were consecutively recruited from a large psychiatric hospital in Wuhan, China, and administered a self-report questionnaire, which comprised standardized questions regarding sociodemographics, COVID-19 vaccination status, attitudes toward COVID-19 vaccines, and psychopathology. Vaccine-recipients were additionally asked to report adverse events that occurred following vaccination. PwMDs had a much lower rate of vaccination than Wuhan residents (10.8% vs. 40.0%). The rates of vaccine acceptance and hesitancy were 58.1% and 31.1%, respectively. Factors associated with vaccine uptake included having other mental disorders (odds ratio [OR] =3.63), believing that ≥50% of vaccine-recipients would be immune to COVID-19 (OR=3.27), being not worried about the side effects (OR=2.59), and being an outpatient (OR=2.24). Factors associated with vaccine acceptance included perceiving a good preventive effect of vaccines (OR=12.92), believing that vaccines are safe (OR=4.08), believing that ≥50% of vaccine-recipients would be immune to COVID-19 (OR=2.20), and good insight into the mental illness (OR=1.71). Adverse events occurred in 21.4% of vaccine-recipients and exacerbated pre-existing psychiatric symptoms in 2.0% of vaccine-recipients. Nevertheless, 95.2% of vaccine-recipients rated adverse events as acceptable. Compared to the 58.1% vaccine acceptance rate and the 40.0% vaccination rate in the general population, the 10.8% vaccine coverage rate suggested a large unmet need for COVID-19 vaccination in Chinese PwMDs. Strategies to increase vaccination coverage among PwMDs may include provision of reliable sources of information on vaccines, health education to foster positive attitudes toward vaccines, a practical guideline to facilitate clinical decision-making for vaccination, and the involvement of psychiatrists in vaccine consultation and post-vaccination follow-up services.